Rising incidence and high mortality in intentional sodium nitrite exposures reported to US poison centers. (2nd December 2021) - McCann, Sean D.; Tweet, Marit S.; Wahl, Michael S.
Abstract: Introduction: Sodium nitrite is an oxidizing agent capable of producing profound methemoglobinemia. Large quantities of sodium nitrite can be purchased online, and recent literature has identified several cases of intentional self-poisoning, including multiple cases of mortality. This has raised concern that intentional sodium nitrite poisoning and resultant severe methemoglobinemia may be increasing in incidence and could represent a substantial public health threat. Materials and methods: This study used data obtained from the National Poison Data System (NPDS) to evaluate the incidence and mortality rate of intentional sodium nitrite poisoning of suicidal intent reported to US poison centers over a five-year period. Patient demographics, exposure characteristics, treatments administered, and patient outcomes were analyzed. Temporal patterns in exposure were also investigated. Results: Forty-seven cases were identified in the NPDS database, of which three were excluded due to lack of outcome data. Median patient age was 23 years, 52% of patients were female and 86% of exposures occurred at the patient's residence. Serious outcomes were observed in 84% of cases, 77% of patients included were treated with methylene blue and 30% of patients died. No intentional sodium nitrite exposures were reported in the first two years studied, but we observed an increase in the incidence of exposures reported through the remainder of the investigation period. Discussion/conclusions: The incidence of intentional self-poisoning with sodium nitrite has been increasing since 2017. Many of these exposures result in toxicity requiring antidotal therapy, and a high mortality rate was observed. Recent literature indicates that this trend may be the result of ready access to this poison through online vendors combined with recommendations shared in online communities that sodium nitrite be used as an effective method of suicide. Further study is needed to better characterize this phenomenon and develop public health interventions to prevent future morbidity and mortality.